LEARNERS’ PERSPECTIVE TOWARDS SELF-REGULATED LEARNING STRATEGY FOR ENHANCING ESSAY WRITING - Novriyani; Rizki Anugrah PR (Teaching English and Language Learning English Journal, 2025)
Self-regulated learning (SRL) has been widely recognized as a critical component in supporting learners’ academic development, particularly in complex language production tasks susch as essay writing. This research aims to investigate students’ perceptions of SRL strategy use and its contribution to enhanching essay writing performance. Employing a quantitative descriptive design, data were collected from 15 participants through a validated SRL questionnaire consisting of 32 items representing forethought, performance, and self-reflection phases. The findings indicate that learners demonstrate a generally high level of engagement in SRL, with the strongest responses observed in goal-setting, task planning, self-monitoring, and reflective evaluation. Students reported that SRL strategies helped them organize ideas more effectively, amnage writing tasks more independently, and improve the clarity and coherence of their essays. Additionally, learners perceived the self-reflection phase as particularly influential, as it enabled them to identify weaknesses, intehgrate feedback, and plan targeted improvements. The research contributes to a deeper understanding of SRL in the context of academic writing and provides implications for teaching strategies that promote learners autonomy and sustained writing proficiency. Key words: Essay Writing, Learners’ Perspective, Self-Regulated Learning Strategy